Metaphor in Illness Writing Fight and Battle Reused - Wohlman, Anita (Edinburgh University Press, 2022)
Listen to the interview with Anita Wohlmann about Metaphor in Illness Writing in New Books Network here. Metaphor in Illness Writing argues that even when a metaphor appears problematic and limiting, it need not be dropped or dismissed. Metaphors are not inherently harmful or beneficial; instead, they can be used in unexpected and creative ways. This book analyses the illness writing of contemporary North American writers who reimagine and reappropriate the supposedly harmful metaphor 'illness is a fight' and shows how Susan Sontag, Audre Lorde, Anatole Broyard, David Foster Wallace and other writers turn the fight metaphor into a space of agency, resistance, self-knowledge and aesthetic pleasure. It joins a conversation in Medical Humanities about alternatives to the predominance of narrative and responds to the call for more metaphor literacy and metaphor competence."